Pengaruh Pemanfaatan Instagram Sebagai Social Media Marketing dalam Membangun Brand Awareness : Studi Kasus Pada Akun @Pempek.lola8 Kota Bengkulu - Nurjanie, Ahmad Yoga; Syofian, Syofian; Hidayati, Arifah (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine how much influence the influence of Profile, New Feed and Homepage on consumer visits on pempek.lola8 Bengkulu city. The method in this research is quantitative research. The sampling technique is purposive sampling. In this study the data comes from distributing questionnaires (Google Form) which will be distributed online to consumers who have purchased pempek lola. The population of this study are consumers who have purchased pempek lola, researchers use the hair formula where 19 indicators x 5 = 95 respondents. The results of this study are; (1) Profile partially affects consumer visits to pempek.lola8 city of bengkulu, (2) New Feed partially affects consumer visits to “pempek.lola8 city of bengkulu (3) Homepage partially affects consumer visits to pempek.lola8 city of bengkulu (4) Profile, New Feed and Homepage on consumer visits to pempek.lola8 city of bengkulu simultaneous influence.